Diffuse Matter from Star Forming Regions to Active Galaxies A Volume Honouring John Dyson - Hartquist, T.W.; Pittard, J. M.; Falle, S.A.E.G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
John Dyson has contributed to the study of the hydrodynamic processes that govern a wide variety of astrophysical sources which he has helped explain. In this volume dedicated to him, introductory reviews to a number of the key processes and to the sources themselves are given by leading experts. The mechanisms in which the multi-component natures of media affect their dynamics receive particular attention, but the roles of hydromagnetic effects are also highlighted. The importance of cosmic ray moderation and mass transfer between different thermal phases for cosmic ray moderation and mass transfer between different thermal phases for the evolution of flows are amongst the topics treated. The main types of regions considered include those where stars form, the circumstellar environments of evolved stars, the larger scale interstellar structures caused by the mass loss of stars, and those where the lines of AGNs form. The reviews complement one another and together provide a coherent introduction to the astrophysics of diffuse sources suitable for postgraduate students and researchers in astrophysics. Individual reviews stand alone and are suitable for an audience that includes advanced undergraduates doing final year projects.
Star Forming Regions -- Numerical Simulations of Star Formation -- Molecular Astrophysics of Star Formation -- Dusty Plasma Effects in Star Forming Regions -- Massive Star Formation -- Spectropolarimetry and the Study of Circumstellar Disks -- How to Move Ionized Gas: An Introduction to the Dynamics of HII Regions -- MHD Ionization Fronts -- Herbig-Haro Jets from Young Stars -- Hypersonic Molecular Shocks in Star Forming Regions -- The Effects of Evolved Stars on Their Environments -- Wind-Blown Bubbles around Evolved Stars -- Do Fast Winds Dominate the Dynamics of Planetary Nebulae? -- Spectral Studies of Supernova Remnants -- Multicomponent Flows and Cosmic Rays -- Mass-Loaded Flows -- The Effects of Cosmic Rays on Interstellar Dynamics -- The Status of Observations and Speculations Concerning Ultra High-Energy Cosmic Rays -- Starburst Galaxies and Active Galactic Nuclei -- The Messier 82 Starburst Galaxy -- Active Galactic Nuclei.
Keywords: Astronomy; Astrophysics; Observations, Astronomical; Astronomy—Observations.; Astronomy, Astrophysics and Cosmology; Astronomy, Observations and Techniques; Astrophysics and Astroparticles